Systematic review of evidence on the association between personality and tinnitus - Mucci,Samantha (2014)
INTRODUCTION: The scientific literature that personality traits are associated with the individual's adaptation to chronic diseases, becoming an important factor in the etiology and prognosis of physical illness. Some studies indicate that personality characteristics may influence the perception of tinnitus. OBJECTIVE: To assess the scientific evidence of the association between tinnitus and personality. METHODS: A systematic review in the following databases: PubMed, SciELO, LILACS and Web of knowledge. Were selected only studies with patients older than 18 years, published in English, Portuguese or Spanish who established an association between tinnitus and personality. RESULTS: Seventeen of the 77 articles found were selected: 13 cross-sectional studies, two longitudinal studies, one validation study, and one birth cohort study. The samples ranged from 27 to 970 patients. CONCLUSION: Some personality traits, especially neuroticism, psychasthenia, and schizoid aspects, may be associated with tinnitus perception and with the annoyance due to this symptom.